DIGITAL PROPAGANDA AND DISINFORMATION GENERATED VIA ARTIFICIAL INTELLIGENCE: THE ISRAEL/PALESTINE CONFLICT AND THE FALL OF BASHAR AL-ASSAD IN SYRIA CASE STUDIES - Kazić, Tanja (The Policy of National Security, 2025)
In this paper, the author will analyze the role of digital propaganda and disinformation generated via artificial intelligence (AI) in the ongoing Middle Eastern conflicts, with a focus on the escalation of conflict between Israel and Palestine, as well as the overthrow of the President of the Syrian Republic Bashar al-Assad. In this geographical framework, the author will examine how technologies based on AI, and primarily the generation of deepfake materials, have a use value in conflict zones, tracing the first steps of use of such tactics for war purposes in the ongoing Russia-Ukraine conflict. By confirming the presence and influence of this type of cyber operations through the analysis of two case studies, the author will confirm the hypothesis, which states that contemporary digital propaganda, aided and generated via AI, significantly complicates the course of ongoing events, thus leading to inevitable conflict escalation, making it difficult to distinguish the truth from lies, in both military and political context. With the use of the content analysis method, focused on the identification of instances of placement of AI-generated digital propaganda, this paper will present a comprehensive analysis and study of individual cases of Israel/Palestine and the Syrian Republic to create a framework of possibilities and influence of such content on classical armed conflicts, as well as on political crises in the Middle East.